2018
DOI: 10.1371/journal.ppat.1006920
|View full text |Cite
|
Sign up to set email alerts
|

RSV hijacks cellular protein phosphatase 1 to regulate M2-1 phosphorylation and viral transcription

Abstract: Respiratory syncytial virus (RSV) RNA synthesis occurs in cytoplasmic inclusion bodies (IBs) in which all the components of the viral RNA polymerase are concentrated. In this work, we show that RSV P protein recruits the essential RSV transcription factor M2-1 to IBs independently of the phosphorylation state of M2-1. We also show that M2-1 dephosphorylation is achieved by a complex formed between P and the cellular phosphatase PP1. We identified the PP1 binding site of P, which is an RVxF-like motif located n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 62 publications
0
83
0
2
Order By: Relevance
“…Similarly, cellular proteins that could be involved in mRNA translation, in the activity of the polymerase complex, the dynamics of IBs, or in the control of host immune response were shown to concentrate within IBs. More specifically for RSV, the poly(A)-binding protein (PABP) and the translation initiation factor eIF4G ( 19 ), cellular proteins involved in posttranslational modifications such as the phosphatase PP1 (protein phosphatase 1) ( 20 ), the chaperones HSP90 and HSP70 ( 21 , 22 ), actin and actin-associated proteins ( 23 , 24 ), and the proteins involved in antiviral responses MDA5 (melanoma differentiation-associated gene 5) and MAVS (mitochondrial antiviral signaling) ( 25 ) were shown to colocalize within IBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cellular proteins that could be involved in mRNA translation, in the activity of the polymerase complex, the dynamics of IBs, or in the control of host immune response were shown to concentrate within IBs. More specifically for RSV, the poly(A)-binding protein (PABP) and the translation initiation factor eIF4G ( 19 ), cellular proteins involved in posttranslational modifications such as the phosphatase PP1 (protein phosphatase 1) ( 20 ), the chaperones HSP90 and HSP70 ( 21 , 22 ), actin and actin-associated proteins ( 23 , 24 ), and the proteins involved in antiviral responses MDA5 (melanoma differentiation-associated gene 5) and MAVS (mitochondrial antiviral signaling) ( 25 ) were shown to colocalize within IBs.…”
Section: Introductionmentioning
confidence: 99%
“…This protein has a modular organization with a central coiled-coil domain involved in oligomerization, flanked by two intrinsically disordered regions (IDRs) (positions 1 to 130 and 152 to 241) ( 31 , 32 ). A nuclear magnetic resonance (NMR) study of P recently revealed that the N- and C-domains adopt transient secondary structures in solution ( 33 ) and that several of these transient regions correspond to domains of interaction of P with N 0 , M2-1, and L ( 20 , 31 , 34 , 35 ). The interactions between N and P are also well described.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic phosphorylation of the M2-1 protein from respiratory syncytial virus regulates viral transcription. M2-1 is a transcriptional processivity factor whose function is proposed to require cycles of phosphorylation and dephosphorylation by cellular enzymes [ 3 , 4 ]. Phosphorylation also regulate global RNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The RSV Minigenome and plasmids expressing RSV L, N, P, and M2-1 proteins were described previously (30). pGEM3-Gaussia/Firefly encodes a sub-genomic RSV replicon.…”
Section: Methodsmentioning
confidence: 99%